One-pot synthesis of metal-free, yellow-emitting phosphor with organic single crystal as a matrix. (September 2021) - Zhou, Shengju; Lu, Dandan; Sun, Xiaofeng; Yin, Keyang; Zhang, Geping; Chen, Mengjun; Li, Hongguang
Abstract: In recent years, there is a rapid growth on the research of metal-free phosphor. A typical example is blend of photoluminescent carbon nanomaterials with a matrix. Normally, the C dots were prepared first, which were then mixed with the matrix. A drawback of this strategy is that multiple steps have to be involved, which is time consuming. In this work, we show that by simply heating a readily-available small organic molecule (phthalic acid) in a high-boiling solvent with reactive group (formamide), ready-to-use and metal-free phosphor can be produced in high yields (over 70%). The phosphor contains single crystals of phthalic anhydride with photoluminescent species adsorbed on the surfaces, which shows yellow emission in solid state with a fluorescence quantum yield ( Φ ) of 28.53%. The phosphor can be directly used to prepare light-emitting diodes (LEDs), which results in a yellow LED on the UV chip and a white LED on the blue-emitting chip. Graphical abstract: Single crystals of small organic molecules with carbon dots adsorbed on the surface have been prepared. The hybrid material shows yellow emission, which can be used as metal-free phosphor for white-light-emitting diodes. Image 1 Highlights: Metal-free phosphor can be readily prepared in one-step with high yield. The phosphor can be directly used to prepare LEDs. On the blue-emitting LED chip, a white LED was obtained. The as-prepared crystals exhibit strong emission in both solid and colloidal state.